CSF MicroRNAs Reveal Impairment of Angiogenesis and Autophagy in Parkinson Disease. (12th December 2021) - Fowler, Alan J.; Ahn, Jaeil; Hebron, Michaeline; Chiu, Timothy; Ayoub, Reem; Mulki, Sanjana; Ressom, Habtom; Torres-Yaghi, Yasar; Wilmarth, Barbara; Pagan, Fernando L.; Moussa, Charbel
Abstract : Background and Objectives: We assessed longitudinal changes in CSF microRNAs (miRNAs) in patients with moderately severe Parkinson disease. Methods: We used next-generation whole-genome miRNA sequencing to determine CSF miRNA expression in 75 patients with Parkinson disease after single random ascending doses of nilotinib and longitudinal miRNA expression after daily nilotinib, 150 and 300 mg, vs placebo for 1 year. Results: Significant changes in the expression of miRNAs that control genes and pathways that regulate angiogenesis, autophagy, and the blood-brain-barrier components, primarily collagen, were observed over 1 year, suggesting impairment of these pathways in Parkinson progression in these patients. Different miRNAs that indicate activation of genes associated with autophagy flux and clearance and angiogenesis were significantly altered in the nilotinib, 300 mg vs 150 mg, or placebo group, and these changes correlated with clinical outcomes. No changes were observed in miRNAs after a single dose of nilotinib vs placebo. Discussion: This study suggests vascular and autophagy defects in Parkinson progression. Nilotinib, 300 mg, reverses these effects via alteration of miRNA expression, suggesting epigenomic changes that may underlie long-term disease-modifying effects. Trial Registration Information: Clinical trial registration number: NCT02954978.